TINJAUAN EFEKTIVITAS PELAPORAN SPT PPh TAHUNAN DAN KONTRIBUSINYA TERHADAP PENERIMAAN PPH DALAM SKALA NASIONAL - Norman Duma Sitinjak (Ma Chung Press, 2015)
Acceptance of our country is very dependent on Tax Revenue. For the Government ensures that the Tax Receipts can be bigger from year to year. Of several types of taxes, the income tax is the largest contributor. Effectiveness in reporting annual income tax returns from year to year is expected to further rise, the aim is that income tax revenue also continued to rise. The effectiveness reporting annual income tax returns need to be contribution to the effectiveness of the income tax revenue. The goal is to be known objectively the impact of annual income tax returns reporting the effectiveness of the Income Tax.